A Critique of Positive Responsibility in Computing. - Stieb, James A. (Science & Engineering Ethics, 2008)
It has been claimed that (1) computer professionals should be held responsible for an undisclosed list of “undesirable events” associated with their work and (2) most if not all computer disasters can be avoided by truly understanding responsibility. Programmers, software developers, and other computer professionals should be defended against such vague, counterproductive, and impossible ideals because these imply the mandatory satisfaction of social needs and the equation of ethics with a kind of altruism. The concept of social needs is debatable with no one possessing the authority to impose their version of them. Similarly, the notion of “positive responsibility” is difficult to apply, does not effectively change computing practice, and confuses good (i.e., efficient) computer engineering with good (i.e. moral) computer engineering.